Building schemes to facilitate translation: a study of Spanish-Chinese simultaneous interpretation in diplomatic contexts - Xiaoyu, Li (Sinología hispánica. China Studies Review, 2022)
With the increase of China’s international status and influence, the subjects in international exchanges no longer remain at macro level, while shifting towards a more professional and concrete dimension. This paper takes the Spanish-Chinese simultaneous interpretation in political/diplomatic activities as an example, departing from the perspective of Schema Theory and incorporated with the author’s own interpreting training, teaching and practical experience. It aims at putting forward certain translating concepts and coping tactics, highlighting the virtue of knowledge or content schema in interpreting, especially in the practice and training of simultaneous interpretation, hoping to provide some reference to instructors and practitioners in translation education and for career development.